The In-Situ Epoxidation of Rubber Seed Oil (Hevea brasiliensis) by Peroxyacids - Eni Budiyati; Auliya Rahmah; Nur Ahmad Fauzi (Engineering Proceedings, 2025)
This paper adds to the sustainable materials field by in-situ epoxidation of rubber seed oil (RSO), a highly underutilized resource that has been sporadically used, using an optimized combination of 30% hydrogen peroxide and acetic/formic acid sulfuric acid. Most of the previous studies deal with more common vegetable oils, where the main focus in most is given to the epoxidation of these oils and their derivatives. The RSO contained a high iodine value around 135.36 g–I2/100 g. The central to this work is the systematic study of the oxirane number as a function of reaction temperature and the double bond:RCOOH:H2O2 molar ratios. By testing the temperatures of 40, 50, 60, and 70 °C and three specific molar ratios (1:0.6:1.4, 1:1:2, and 1:1.5:3), this research not only found the optimal conditions for epoxidation but also gave valuable information on the reaction kinetics of rubber seed oil. The results showed that a temperature of 60 °C with a 1:1:2 molar ratio gave the highest oxirane number, especially with performic acid, which was 3.200 mmol/g. Then, overall, formic acid consistently outperforms acetic acid in terms of product yields, facilitating a more effective epoxidation process.